Real-time monitoring of the evolving morphology and molecular structure at an organic-inorganic semiconductor interface: SnPc on GaAs(001) - Evans, D; Vearey-Roberts, A; Roberts, O; Brieva, A; Bushell, A; Williams, G; Langstaff, D; Cabailh, G; McGovern, I (2010)
An organic-III-V hybrid semiconductor interface has been studied using real-time photoelectron spectroscopy and x-ray absorption spectroscopy to reveal the evolving morphology and molecular structure within the organic layer during thin film growth. This new approach to in situ characterization has been enabled by electron detection using a direct electron-counting array detector coupled to a hemispherical electron analyzer. The nonplanar tin phthalocyanine (SnPc) molecules initially form a uniform layer within which they have a distinct molecular orientation relative to the S-passivated gallium arsenide substrate surface [GaAs:S(001)]. The critical thickness of 0.9 nm that marks the transition between layered and clustered growth, determined from the photoemission measurements, corresponds to a single molecular layer with the molecules oriented at an angle of (39 ± 2)° to the substrate plane. This value is confirmed by angle-resolved near-edge x-ray absorption fine structure measurements in the same experimental environment. However, the angle is less for the thicker films as the molecule-molecule interaction dominates over the molecule-substrate interaction and the structure is close to that of the bulk triclinic SnPc crystal. © 2010 American Vacuum Society.